THE GREATEST AND SMALLEST VALUES OF A FUNCTION ON A SEGMENT - Sabohat Eshmetova; Mamatqobil Esonturdiyev (Web of Journals Publishing, 2024)
this article discusses about the greatest and smallest values of a function on a segment.
Keywords: greatest, smallest, values, function, segment.